Articulations of educational demands made (im)possible by antagonism to “cultural Marxism” - Lopes, Alice Casimiro (Education Policy Analysis Archives, 2019)
Based on Laclau and Mouffe's theory of discourse, it is presented a discussion about the identifications in educational policies, questioning the essentialism of the political analyses that focus on social groups with pre-constituted identities. To this end, the conservative and ultraliberal educational demands that move in the game of discursive articulations, disarticulations and rearticulations in the educational field, after presidential elections of 2018, made (im)possible by the antagonism to “cultural Marxism”. The “cultural Marxism”, in turn, is made equivalent to the science, especially the social science and the humanities, and the public university. I present this interpretation, aiming at other ways of thinking (and doing) the educational policy or even any policy, in order to question the fundamentalisms of fixed identities and non-contingent projects.